Comparative Efficacy of Various Sources and Rates of Phosphate Rocks to Oil Palm Seedlings - Lubis, Muhammad Edwin Syahputra (1997)
Phosphate Rocks (PR) from various geographical locations are being imported into the Malaysian market mainly from Algeria, North Carolina (USA), Tunisia, China etc. PR vary widely in their physical, chemical and mineralogical properties. Consequently, the solubility and agronomic effectiveness of PR sources also vary widely. In addition, the agronomic effectiveness of PR depends on interactions between several factors, particularly PR material characteristics, soil properties, crop characteristics, and environmental conditions. Hence, There is a need to evaluate the efficacy of various sources of PR as phosphate source for plant growth. In \tiew of this, a glasshouse experiment using oil palm seedlings and a laboratory incubation experiment were used to evaluate the efficacies of these sources of PR The study was undertaken with the following objectives : 1. to assess the solubility of PR in soil by various solubility tests. 2. to evaluate the dissolution of PR sources in an acid Malaysian soil, using an incubation experiment 3. to determine the relative agronomic effectiveness of PRs to oil palm seedlings in glasshouse experiment. 4. to characterize the immediate and residual availability of PR using the E-value approach.